High susceptibility to zoliflodacin and conserved target (GyrB) for zoliflodacin among 1209 consecutive clinical Neisseria gonorrhoeae isolates from 25 European countries, 2018. (10th February 2021) - Unemo, Magnus; Ahlstrand, Josefine; Sánchez-Busó, Leonor; Day, Michaela; Aanensen, David; Golparian, Daniel; Jacobsson, Susanne; Cole, Michelle J; ,
Abstract: Objectives: Novel antimicrobials for treatment of gonorrhoea are imperative. The first-in-class spiropyrimidinetrione zoliflodacin is promising and currently in an international Phase 3 randomized controlled clinical trial (RCT) for treatment of uncomplicated gonorrhoea. We evaluated the in vitro activity of and the genetic conservation of the target (GyrB) and other potential zoliflodacin resistance determinants among 1209 consecutive clinical Neisseria gonorrhoeae isolates obtained from 25 EU/European Economic Area (EEA) countries in 2018 and compared the activity of zoliflodacin with that of therapeutic antimicrobials currently used. Methods: MICs of zoliflodacin, ceftriaxone, cefixime, azithromycin and ciprofloxacin were determined using an agar dilution technique for zoliflodacin or using MIC gradient strip tests or an agar dilution technique for the other antimicrobials. Genome sequences were available for 96.1% of isolates. Results: Zoliflodacin modal MIC, MIC50, MIC90 and MIC range were 0.125, 0.125, 0.125 and ≤0.004–0.5 mg/L, respectively. The resistance was 49.9%, 6.7%, 1.6% and 0.2% to ciprofloxacin, azithromycin, cefixime and ceftriaxone, respectively. Zoliflodacin did not show any cross-resistance to other tested antimicrobials. GyrB was highly conserved and no zoliflodacin gyrB resistance mutations were found. No fluoroquinolone target GyrA or ParC resistance mutations or mutations causing overexpression of the MtrCDE efflux pump substantially affected the MICs of zoliflodacin. Conclusions: The in vitro susceptibility to zoliflodacin was high and the zoliflodacin target GyrB was conserved among EU/EEA gonococcal isolates in 2018. This study supports further clinical development of zoliflodacin. However, additional zoliflodacin data regarding particularly the treatment of pharyngeal gonorrhoea, pharmacokinetics/pharmacodynamics and resistance selection, including suppression, would be valuable.